2010
DOI: 10.4085/1062-6050-45.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Parenthood and Working of Female Athletic Trainers in the Secondary School and Collegiate Settings

Abstract: Context: Female athletic trainers (ATs) are currently underrepresented in the collegiate setting. Parenting and family obligations may play a role in this underrepresentation.Objective: To examine female ATs' perspectives on parenting and working in the secondary school and collegiate employment settings.Design: Cross-sectional study. Setting: Online survey. Patients or Other Participants: A total of 1000 nonstudent, female certified ATs who were currently members of the National Athletic Trainers' Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
83
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(89 citation statements)
references
References 7 publications
4
83
2
Order By: Relevance
“…[1][2][3]5 It is an unfortunate reality that female ATs make up only approximately 28% of the full-time collegiate staff. 5 This is especially concerning when the National Athletic Trainers' Association indicates that more than 50% of its members are female. 6 A relationship appears to exist between balancing professional responsibilities with parenthood and retention factors, especially for those who leave the collegiate clinical setting to work in clinical settings more favorable to family life.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]5 It is an unfortunate reality that female ATs make up only approximately 28% of the full-time collegiate staff. 5 This is especially concerning when the National Athletic Trainers' Association indicates that more than 50% of its members are female. 6 A relationship appears to exist between balancing professional responsibilities with parenthood and retention factors, especially for those who leave the collegiate clinical setting to work in clinical settings more favorable to family life.…”
mentioning
confidence: 99%
“…4 Hypothetically, the decline in the number of female ATs in the profession has been linked to the desire to strike a balance among work responsibilities, personal interests, and family obligations. [1][2][3]5 Concerns about work-life balance (WLB) and time for parenting have been found to influence decisions to persist within the collegiate levels, as the job responsibilities often include long hours (.40 h/wk) and travel, which can limit time spent at home with family. [1][2][3]5 It is an unfortunate reality that female ATs make up only approximately 28% of the full-time collegiate staff.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,9 In fact, long work hours negatively affect the professional commitment of female ATs, who often change employment settings or leave the profession to achieve WLB. 3,10,11 Researchers [12][13][14] have indicated that individuals differ in their experiences of WLB and abilities to cope because of differences in individual characteristics in a given context. These individual characteristics include values, personality, coping skills, support systems, and sex.…”
mentioning
confidence: 99%
“…For example, athletic training jobs can be similar in the types of role strain employees face (lack of control over schedules, hours, and travel; perceived inadequate compensations; and overall job demands), but in a recent study, Naugle et al 15 demonstrated that women reported a higher incidence of burnout than their male counterparts even though the male ATs worked more hours on average than the female ATs. Researchers 3,4,9,10 examining retention and WLB in female ATs have identified the time commitment of the profession, particularly in the collegiate setting, as problematic, especially for ATs trying to balance motherhood and athletic training.…”
mentioning
confidence: 99%